Antecedents and outcome of Waqif's trust in Waqf Institution - Hasan, Rashedul; Siraj, Siti Alawiah; Mohamad, Muslim Har Sani (Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2017)
This study is undertaken to determine the ability of Waqf institutions toward influencing Waqf's trust and commitment. The stakeholder trust model for Waqf institution proposed by Hassan & Siraj (2017) was empirically tested with a sample of fifty-four Waqif's of public waqf institution in Bangladesh. Results from Structural Equation Modelling (SEM) using PLS 3.0 provided statistical validity of the model. Among the three components of board attributes, only board integrity has a statistically non-significant impact on Waqif's trust. While board opportunism negatively affects trust, communication and accountability are found to have a positive association with Waqif's trust. Trust is also found to have positive a positive impact on commitment. The established model does not consider social, economic and psychological dimensions that might determine Waqif's trust and commitment toward public Waqf institutions. Results provided by the study will allow policy makers to focus on key issues that facilitate in developing trust and commitment between Waqif and Waqf institution. This study is the first to empirically test the commitment-trust theory in the context of waqf operating in a South-East Asian country using Structural Equation Modelling technique.